Hybrid greedy algorithms for fuzzy tardiness/earliness minimisation in a special single machine scheduling problem: case study and generalisation - Niroomand, Sadegh; Hadi-Vencheh, Abdollah; Mirzaei, Nima; Molla-Alizadeh-Zavardehi, Saber (Taylor & Francis Ltd, 2016)
This paper focuses on earliness and tardiness minimisation of a special case of single machine scheduling problem with common fuzzy due-date. The problem arises from a cable manufacturing system where cables are produced in different sizes and colours. The problem is generalised by considering two attributes for each product (job) and different levels for each attribute. Setup time between a pair of jobs is different when the level of one attribute or both attributes is changed, as is the case in this study. Three hybrid greedy algorithms and a genetic algorithm are introduced to solve the test problems generated for the generalised problem while Taguchi experimental design method is used to find the best level of parameters for each algorithm. Finally, the comparisons are employed to select the best method.
Keywords: scheduling problem; meta-heuristic; greedy algorithm; Taguchi method; fuzzy number